Quantitative measurement of mechanical properties in wound healing processes in a corneal stroma model by using vibrational optical coherence elastography (OCE) - Zhang, Yilong (Biomed Opt Express, 2020)
Corneal wound healing, caused by frequent traumatic injury to the cornea and increasing numbers of refractive surgeries, has become a vital clinical problem. In the cornea, wound healing is an extremely complicated process. However, little is known about how the biomechanical changes in wound healing response of the cornea. Collagen-based hydrogels incorporating corneal cells are suitable for replicating a three-dimensional (3D) equivalent of the cornea in-vitro. In this study, the mechanical properties of corneal stroma models were quantitatively monitored by a vibrational optical coherence elastography (OCE) system during continuous culture periods. Specifically, human corneal keratocytes were seeded at 5 × 10(5) cells/mL in the hydrogels with a collagen concentration of 3.0 mg/mL. The elastic modulus of the unwounded constructs increased from 2.950 ± 0.2 kPa to 11.0 ± 1.4 kPa, and the maximum thickness decreased from 1.034 ± 0.1 mm to 0.464 ± 0.09 mm during a 15-day culture period. Furthermore, a traumatic wound in the construct was introduced with a size of 500 µm. The elastic modulus of the neo-tissue in the wound area increased from 1.488 ± 0.4 kPa to 6.639 ± 0.3 kPa over 13 days. This study demonstrates that the vibrational OCE system is capable of quantitative monitoring the changes in mechanical properties of a corneal stroma wound model during continuous culture periods and improves our understanding on corneal wound healing processes.